ANTIOXIDANT PROPERTIES OF SOME SEASONAL LEAFY VEGETABLES FROM RATNAGIRI DISTRICT OF MAHARASHTRA - L. A. KAGALE; A. B. SABALE (International Journal of Pharma and Bio Sciences, 2013)
Analysis of antioxidant potential of seasonal vegetables occurring in Ratnagiri district and which are a part of regular diet and also possess medicinal properties was undertaken. Methanolic, ethanolic and aqueous extracts of five wild vegetables namely Colocasia esculenta (L.), Clerodendrum serratum (L.), Cassia tora (L.), Celosia argentea (L.) and Amorphophallus paeoniifolius (Dennst.) were prepared for estimating various antioxidant properties such as DPPH, FRAP, FICA and reducing power assay. Total phenolic content of the vegetable extracts was also determined in order to understand the correlation with antioxidant properties. Results revealed that all the vegetables possess a substantial antioxidant potential and can add to the nutritional supplement when consumed in the daily diet. DPPH, FRAP and FIC activities were maximum in the methanol and ethanol extracted samples whereas reducing ability was greater in the aqueous extracts of vegetables.